Use of cholesterol-loaded cyclodextrin: An alternative for bad cooler stallions - Hartwig, F. P. [UNESP]; Lisboa, F. P. [UNESP]; Hartwig, F. P.; Monteiro, G. A. [UNESP]; Maziero, R. R. D. [UNESP]; Freitas-Dell'Aqua, C. P. [UNESP]; Alvarenga, Marco Antonio [UNESP]; Papa, Frederico Ozanam [UNESP]; Dell'aqua Junior, José Antônio [UNESP] (Elsevier B.V., 2014)
During the cooling process, sperm may suffer irreversible damage that compromises the fertility rate. Incorporating cholesterol-loaded cyclodextrin (CLC) represents a strategy to increase sperm resistance at low temperatures; however, high levels of cholesterol in the cell membrane can interfere with sperm capacitation. The goals of this study were to determine the CLC concentration and cooling temperature that produce optimal kinetic parameters and viability of sperm from stallions identified as bad coolers (BCs) and good coolers (GCs), as well as the effect of adding CLC on the occurrence of the acrosome reaction (ACR) and on the fertility rate of cooled sperm. In experiment 1, each ejaculate was divided into four groups: Control and treated with 1 (CLC-1), 1.5 (CLC-1.5), or 2 mg (CLC-2) of CLC/120 x 10(6) sperm and cooled for 48 hours at 5 degrees C. In experiment 2, each ejaculate was divided into four groups: Control and CLC-1.5 cooled at 15 degrees C or 5 degrees C for 24 hours. For experiment 3, GC and BC stallions were used, and the ejaculates were divided into control and CLC-1.5 cooled at 5 degrees C for 48 hours. According to experiment, the sperm kinetics (SK) and plasma membrane integrity (PMI) were analyzed before and after 24 and 48 hours of cooling. In experiment 4, the ejaculates were divided into four groups: Control and CLC-1.5 maintained at room temperature or cooled at 5 degrees C for 24 hours. Each group was incubated with ionophore calcium at 37 degrees C for 3 hours. The incidence of ACR was analyzed before and after 1, 2, and 3 hours of incubation. For experiment 5, two cycles of 10 mares for a GC stallion and two cycles of 25 for a BC stallion were used. The inseminations were performed with control and CLC-1.5 groups cooled at 5 degrees C for 24 hours. According to results, all groups treated with CLC exhibited higher PMI compared with controls, and CLC-1.5 and CLC-2 exhibited the best SK results. The cooling temperature of 5 degrees C was superior to 15 degrees C when the sperm was treated with CLC. The GC and BC stallions benefited from the CLC-1.5 treatment, but the BCs were more evident, which presented greatly increased PMI and SK. There was a delay in capacitation of at least 3 hours for the fresh sperm and at least 1 hour for cooled sperm supplemented with CLC-1.5. After adding CLC-1.5, the fertility of BC stallion significantly increased, but that of the GC was not altered. Thus, incorporating CLC is an effective technique to cool equine semen, although it is indicated mainly for BC stallions. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Equine semen; Cooling; Cholesterol; Fertility